Lamego e a sua catedral no Códice 390 da colecção António Capucho (1679-1712): espaços e dinâmicas segundo um livro de despesas do Cabido lamecense - Nuno Resende (2013)
The codex 390 - named after the serial number assigned by auction - acquired from the private collection of António Capucho in 2009, is one of the main and most distinct primary historical sources to the life of the Chapter of Lamego's cathedral. This is one of the books of expenses from that institution, dated between 1679 and 1712, that had already been reported and studied by João Amaral, head of Lamego's museum in 1965. Having disappeared from the local archives, it recently reappeared in a private collection. Our attention for this document focuses on exploring and analysing the abundant statistical and nominal information, which allows us to confront the organization of the chapter with a number of other national institutions in many aspects of their temporal interventions. Our main objective is to understand the dynamics of the Lamego cathedral's chapter by studying and deepening the knowledge about its activity and its individuals/institutions within the period limited by the memory preserved in codex 390, as well as emphasizing the organization of the cathedral within the Catholic Reformation period.